Specificity in the accumulation of fatty acids in adipose tissue of mammals (Revista Española de Fisiología, 1986)
To investigate possible differences in triacylglyceride accumulation in adipose tissue, six different species have been studied (hamster, mouse, rat, rabbit, dog and pig).They were fed the same diet of high proportion of saturated fatty acids during 3 months after the lactation period.There are significant differences between the fatty acids in the diet and the studied tissue, a higher proportion of myristic, palmitoleic and linoleic acids together with a minor proportion of palmitic and stearic acids being accumulated in all studied species except in pig.The differences among species were significant in most cases being maximal in pig (57.7% of saturated fatty acids) and hamster (24.4% of saturated fatty acids).There is a direct relationship between the position of each fatty acid in the triacylglyceride and its proportion in the tissue, this proportion being maximal when the fatty acid is placed on position 2 in the triacylglycerides.There is also a relationship between the different position in the phylogenetic scale of each studied species and the differential fatty acid composition.All these data suggest that there are specific mechanisms involved in the fatty acids accumulation on the adipose tissue.The position of the different fatty acids in the triacylglyceride studied could be a part of this mechanism.